Tetraflavonoid and biflavonoids from Aristolochia ridicula - Machado, Marcos B. [UNESP]; Lopes, Lucia Maria Xavier [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Biflavones, a chalcone-flavone, and a tetraflavonoid with a new carbon skeleton were isolated from the leaves of Aristolochia ridicula. Their structures were determined by chemical derivatizations and spectrometric analyses. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Aristolochia ridicula; Aristolochiaceae; Structural elucidation; Flavonoid; Biflavonoid; Tetraflavonoid; Chalcone-flavone; Ridiculuflavone D; Ridiculuflavonylchalcone B; Ridiculuflavonylchalcone C